Historical Roots of Research in Nanotechnology Application in Dental Composites: A Bibliometric Analysis - Raeisi Estabragh, Sajad; Vosooghinezhad, Behzad; Ghotbi , Nader; Soleimannejad, Hamideh; Sabanik , Pouya; Hashemzadeh, Ali; Lotfhaghpanah, Zahra (Galen Medical Journal, 2024)
Background: The development of nanotechnology in dental composites has revolutionized the field of restorative dentistry. However, the historical roots of this field are not well understood. Materials and Methods: A bibliometric analysis was conducted using the Web of Science database to identify research roots in nanotechnology application in dental composites. A comprehensive search was performed using a specific search syntax, and 863 study data were exported. The data was analyzed using the Bibliometrix R package, and a historical direct citation network was employed to analyze the historical development of the research field. Results: The analysis revealed a moderate growth rate of 18.32% and a high degree of international collaboration in the field. The average age of documents was 6.12 years, with an average of 28.83 citations per document. The study identified key publications and authors that have shaped the development of the research field over time. The analysis highlighted the importance of concepts such as silanization, dual silanization, and interfacial phase reactivity in the development of dental nanocomposites. Additionally, the study found that the development of antimicrobial dental materials has been a significant area of research, with a focus on the use of quaternary ammonium polyethylenimine nanoparticles and silver nanoparticles to inhibit bacterial growth and biofilm formation. Conclusion: This study identified key publications and authors that have shaped the field and highlights the importance of concepts that have driven the development of dental nanocomposites, including antimicrobial properties. The findings of this study can inform future research and development in the field of dental nanocomposites.